ANALISIS PENGARUH INFORMASI KEUANGAN PERUSAHAAN DAN NON KEUANGAN PERUSAHAAN TERHADAP TINGKAT UNDERPRICING SAHAM PERDANA DI BURSA EFEK INDONESIA (Studi empiris pada perusahaan yang IPO periode 2018) - Ulfa Setyaningsih; Theresia Tyas Listyani; Manarotul Fatati (KEUNIS, 2019)
Stock underpricing is a situation where the stock price at the time of supply in the primary market lower than when traded in the secondary market. Stock Underpricing is unfavorable phenomenon for companies that go public, because the funds obtained the company was not optimal. This study aimed to analyze the influence of Earning Per Share (EPS), Debt to Equity Ratio (DER), Underwriter Reputation and Age Companies on the level of Underpricing level at the Indonesia Stock Exchange on the company's IPO period of 2018. The study design was quantitative research applied causal. The sampling technique used was purposive sampling, with a total sample of 54 and data used are cross section. Data analysis method used is multiple linear regression operated by SPSS 20.0. The results of this study indicate that the Earning Per Share (EPS) and Debt to Equity Ratio (DER) have no significant effect on the level of underpricing of IPO at the Indonesia Stock Exchange, while Reputation Underwriter and Age Company have significant effect on the level of underpricing of IPO at the Indonesia Stock Exchange.